2013
DOI: 10.1074/jbc.m113.467977
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Code-guided Protein Synthesis and Folding in Escherichia coli

Abstract: Background: Synonymous codon usage affects protein properties in a given organism. Results: A total of 342 antibody codon variants were identified, differing significantly in solubility and functionality while retaining the identical original amino acid sequence. Conclusion: Genetic codes control protein synthesis and folding. "Codon-preferred" DNA template(s) can be generated by functional screening. Significance: Protein properties can be considerably altered by synonymous codons without substituting amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 29 publications
2
40
0
1
Order By: Relevance
“…In this study, it was demonstrated that scFv encoded by genes with different synonymous codons could be synthesized in E. coli with different solubility and antigen-binding ability. 63 The result in this experiment clearly suggested that the variation in protein structure and function can be brought by varying the synonymous sites in the coding sequence. These experiments clearly demonstrated that synonymous changes are not redundant.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…In this study, it was demonstrated that scFv encoded by genes with different synonymous codons could be synthesized in E. coli with different solubility and antigen-binding ability. 63 The result in this experiment clearly suggested that the variation in protein structure and function can be brought by varying the synonymous sites in the coding sequence. These experiments clearly demonstrated that synonymous changes are not redundant.…”
mentioning
confidence: 78%
“…The authors were more biased to study the impact of synonymous codons on mRNA structure and, therefore, did not provide any information regarding the structure and folding of the green fluorescent protein in E. coli. In this context, Hu et al 63 studied the heterologous expression of anti-IgE single chains (scFv) in E. coli. They constructed the synonymous codon library of the gene.…”
mentioning
confidence: 99%
“…For example, Zhou et al (2013) reported that codon optimization increases FREQUENCY protein (FRQ) expression, alters FRQ phosphorylation and stability, and impairs functions in the circadian feedback loops. Hu et al (2013) also reported that 342 codon variants of scFv antibody differed significantly in protein solubility and functionality without amino acid substitution. In this study, the pBD2 protein expressed by the optimized gene had antimicrobial activity against Gram-positive S. aureus and Gram-negative E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that synonymous codon substitutions influence not only gene expression but also protein structure and function (Hu et al, 2013;Zhou et al, 2013). For example, Zhou et al (2013) reported that codon optimization increases FREQUENCY protein (FRQ) expression, alters FRQ phosphorylation and stability, and impairs functions in the circadian feedback loops.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de ainda restarem algumas questões a respeito da degeneração do processo traducional, uma vez que um mesmo aminoácido pode ser identificado por mais de um códon (sequência de três bases nitrogenadas), o sequenciamento de uma proteína já é obtido mais facilmente. Um fato interessante que se especula a respeito da degeneração é que talvez ela possua relação com o processo subsequente, nomeado folding ou dobramento da proteína (Hu et al, 2013). A este processo será dada especial atenção por conta dos objetivos aqui propostos.…”
Section: Estrutura Proteicaunclassified